Single-Cell Transcriptomic Analysis of Kaposi Sarcoma. - Daniel A Rauch; Paula Valiño Ramos; Mariam Khanfar; John Harding; Ancy Joseph; Anam Fahad; Paul Simonson; Isabel Risch; Obi Griffith; Malachi Griffith; Lee Ratner (PLoS Pathogens)
Kaposi Sarcoma (KS) is a complex tumor caused by KS-associated herpesvirus 8 (KSHV). Histological analysis reveals a mixture of "spindle cells", vascular-like spaces, extravasated erythrocytes, and immune cells. In order to elucidate the infected and uninfected cell types in KS tumors, we examined twenty-five skin and blood samples from sixteen subjects by single cell RNA sequence analyses. Two populations of KSHV-infected cells were identified, one of which represented a CD34-negative proliferative fraction of endothelial cells, and the second representing CD34-positive cells expressing endothelial genes found in a variety of cell types including high endothelial venules, fenestrated capillaries, and endothelial tip cells. Although both infected clusters contained cells expressing lytic and latent KSHV genes, the CD34+ cells expressed more K5 and less K12. Novel cellular biomarkers were identified in the KSHV infected cells, including the sodium channel SCN9A. The number of KSHV positive cells was found to be less than 10% of total tumor cells in all samples and correlated inversely with tumor-infiltrating immune cells. T-cell receptor clones were expanded in KS tumors and blood, although in differing magnitudes. Changes in cellular composition in KS tumors after treatment with antiretroviral therapy alone, or immunotherapy were noted. These studies demonstrate the feasibility of single cell analyses to identify prognostic and predictive biomarkers.